Electricity Demand Forecasting In NTT Province For 2024-2034 Using Software Low Emissions Analysis Platform (LEAP) - Ramaprilo, Vinsensius Ferreri; Likadja, Frans James (Journal of Energy and Electrical Engineering, 2024)
This study aims to electricity demand forecasting and optimize New Renewable Energy (NRE) to supply electrical energy demand in East Nusa Tenggara (NTT) Province 2024-2034 using Low Emissions Analysis Platform (LEAP) Software, considering factors of population growth, economic growth, and government policies related utilization NRE and environment. The method used is a quantitative descriptive end-use model. High, medium, and low scenarios were added to make the research results more adaptive. Moreover, PLTD and PLTU are scenarios that will experience decreased installed capacity until 2034. The results of forecast electricity demand 2024-2034 in NTT Province, for the high scenario increased from 1,448.49 GWh to 2,018.56 GWh with average growth of 3.50%, medium scenario increased from 1,318.91 GWh to 1,595.31 GWh with average growth of 2.06%, low scenario increased from 1,200.10 GWh to 1,359.33 GWh with average growth of 1.39%. Optimization of NRE in the high, medium, and low scenarios shows that NRE can supply electricity demand until 2034.